Thermal and pressure-induced martensitic phase transformations in a Ni-Al alloy modelled by Sutton-Chen embedded atom method - Kazanc, S.; Ozgen, S. (Taylor & Francis Ltd, 2008)
The Ni-Al alloys which exhibit the thermoelastic martensitic phase transformations in the composition range from 60 to 65 atomic percentage (at.%) of Ni are widely used in the high technology applications. In this study, both thermal and pressure-induced phase transformations in Ni-37.5 at.%Al alloy model were investigated by a molecular dynamics (MD) method. Physical interactions between atoms in the alloy system were modelled using the Sutton-Chen version of the embedded atom method based on many-body interactions. The potential parameters for cross interactions between Ni and Al atoms were estimated by optimising the results obtained from the MD simulations, taking into account the experimental data including the crystal lattice properties of the model alloy in high temperature phase.
Keywords: thermoelastic phase transformation; embedded atom method; molecular dynamics simulation; Ni-Al alloy